Temperature cycling analysis for ball grid array package using finite element analysis - Muhammad Nubli, Zulkifli; Zul Azhar, Zahid Jamal, Prof. Dr.; Ghulam, Abdul Quadir (Emerald Group Publishing Limited, 2011)
Link to publisher's homepage http://www.emeraldinsight.com/